2016
DOI: 10.1155/2016/9872561
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Vaginal Stillbirth in the Presence of Placenta Previa at 33 Weeks of Gestation

Abstract: It was demonstrated that second- and third-trimester therapeutic termination of pregnancy (TOP) is feasible in cases with placenta previa. We report a 34-year-old woman with complex fetal malformations associated with placenta previa. An ultrasound examination at 21 weeks of gestation revealed fetal growth restriction (FGR) and complex fetal malformations associated with a placenta previa. After extensive information, the parents opted for careful observation. Thereafter, FGR gradually progressed and we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although fetal death complicated by placenta previa has been reported in several studies 1, 2, 3, no large‐scale study on the management of fetal death with placenta previa has yet been reported. Ploeg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although fetal death complicated by placenta previa has been reported in several studies 1, 2, 3, no large‐scale study on the management of fetal death with placenta previa has yet been reported. Ploeg et al.…”
Section: Discussionmentioning
confidence: 99%